Association Between Lymphocyte Level and Severity of Coronavirus Disease 2019 Patients: A Cross-sectional Study in Indonesia - Buchari, Buchari; Andayani, Hafni; Putri, Nadia Ayunda (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Coronavirus disease 2019 (COVID-19) pandemic has caused significant health problems globally. COVID-19 should be considered a systemic disease since it involves multiple systems, including the hematopoietic system and the immune system. AIM: This study sought to determine the relationship between the lymphocyte levels and the severity of COVID-19 patients in Indonesia. METHODS: A cross-sectional study was conducted among COVID-19 patients at Dr. Zainoel Abidin Hospital Banda Aceh Indonesia from August 27, to September 20, 2021. The subjects were recruited using consecutive sampling method and the data were obtained at their admission to the hospital. Chi-squared test was used to assess the association between lymphocyte levels and the severity of patients. RESULTS: A total of 280 COVID-19 patients included of which 56.9% (91/160) of the patients with moderate severity, 76.1% (51/67) with a severe condition, and 84.9% (45/53) with critical severity had lymphopenia. There were no patients with lymphocytosis found in this study (0%). The Chi-squared test suggested that the lymphocyte level was significant associated with the severity of COVID-19 patients with p < 0.001. CONCLUSION: Our study suggests that the lower the lymphocyte level, the higher the severity of COVID-19 patients. The level of lymphocyte is therefore potentially to be used as predictor for the disease severity and needs to be monitored regularly in COVID-19 patients.